RiTA International Conference focused on future robotic application research - Siti Nurfarmy, Ibrahim (2019)
The Sixth International Conference on Robot Intelligence Technology and Applications (RiTA) that was held in Putrajaya on December 20, 2018 had attracted more than 60 local and international entries.